The Appropriate Third Places: A Perspective from the Muslim Youth - Fath Nadizti; Himasari Hanan; Firmansyah Firmansyah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Third Places refers to managed gathering spaces outside the home and work where people can engage in social interaction voluntarily. These places are known to decrease stress and build a sense of community. However, third places are currently developed in a western cultural context. This paper investigates the role of third places in the context of eastern culture, specifically with Islamic values. Using a qualitative approach, the data was gathered using semi-structured interviews with young Muslim visitors of a coffeehouse in Bandung City. The results illustrate that the coffeehouse is considered a third place. Not only because of its availability for conversation and laughter but also its architectural features that support Islamic practices like praying and maintaining certain proximity with the opposite gender. This study concluded that the cultural framework in which a third place is created is critical.